In-situ modified biosynthetic crystals with lanthanum for fluoride removal based on microbially induced calcium precipitation: Characterization, kinetics, and mechanism. (June 2023) - Zhou, Zhennan; Ali, Amjad; Su, Junfeng; Wang, Zhao; Huang, Tinglin; Li, Tianmeng
Abstract: In this research, in-situ modified biosynthetic crystals with lanthanum (BC–La) were synthesized based on anaerobic microbially induced calcium precipitation (MICP) and investigated its capacity for groundwater defluoridation under various operational conditions. The kinetic and thermodynamic models were simulated to explore the effect of the material on the removal of fluoride ion (F − ) under various parameters (pH, initial concentration of F −, and temperature). BC-La had the maximum F − adsorption capacity of 10.92 mg g −1 and 96.66% removal efficiency. The pseudo-second-order kinetic model and Langmuir isotherm model were the best kinetic and isotherm models for F − removal from BC-La, which indicated that F − were mainly spontaneously removed through chemisorption and adsorption processes. The specific surface area was 54.26 m 2 g −1 and the average pore size was 9.0670 nm. BC-La mainly contained LaCO3 OH, LaPO4, CaCO3, Ca5 (PO4 )3 OH, and F − was mainly removed through ion exchange with the material surface. Moreover, OH −, PO4 3−, and CO3 2− significantly influenced the F − removal. This work suggested a novel method for in-situ modification of anaerobic biosynthetic crystals, which improved the defluoridation effect of traditional biosynthetic crystals, increased the stability of the BC-La and allowed to remove F − from groundwater consistently. Graphical abstract: Image 1 Highlights: Lanthanum can effectively change the specific surface area of biological materials. Lanthanum modified biosynthetic crystals can effectively remove fluoride. Fluoride can be effectively removed in a wide pH range. Fluoride was simultaneously removed by ion exchange and chemisorption.